2008
DOI: 10.1530/rep-07-0434
|View full text |Cite
|
Sign up to set email alerts
|

Low reproductive success in Per1 and Per2 mutant mouse females due to accelerated ageing?

Abstract: Recent studies on mice with mutations in the Clock gene have shown that this mutation disrupts oestrus cyclicity and interferes with successful pregnancy. In order to determine whether two other molecular components of the main clock, namely the period genes, Per1 and Per2, have an effect on the length of the oestrous cycle and the reproductive success, we used Per1-and Per2-deficient females. We show that although fecundity of young adult Per mutant females does not differ from that of wild-type females, midd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
90
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 63 publications
5
90
0
3
Order By: Relevance
“…This is surprising as both female [17] and male (this study; electronic supplementary material, figure S1) Per1 2/2 mice are lighter than their WT controls. Lighter individuals in a given species normally have a higher voice pitch [30,31].…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…This is surprising as both female [17] and male (this study; electronic supplementary material, figure S1) Per1 2/2 mice are lighter than their WT controls. Lighter individuals in a given species normally have a higher voice pitch [30,31].…”
Section: Discussionmentioning
confidence: 65%
“…Deletion of clock genes causes pronounced cognitive and behavioural effects throughout the animal kingdom [41]. Period1-deficient mice display alterations in glucocorticoid rhythmicity [42], addiction [43], muscle strength [44], colonic motility [45], fertility [17,46] and memory [16].…”
Section: (B) Innate Routine Behaviour In Laboratory Micementioning
confidence: 99%
See 1 more Smart Citation
“…66 On the one hand, studies on Per1 or Per2 mutant mice suggested the disruption of circadian rhythms with only minor fertility alterations, such as decreased litter size, increased perinatal mortality, and disruption of the estrus cycle with age. 67,68 In specific, these mutants have normal reproductive function, but fertility rapidly deteriorates with age. In Per1/Per2 null mice, Pilorz and Steinlechner found similar fecundity as in wild type in young adult, but there was lower reproductive success because of the low number of successfully delivered offspring in middleaged mice.…”
mentioning
confidence: 99%
“…In Per1/Per2 null mice, Pilorz and Steinlechner found similar fecundity as in wild type in young adult, but there was lower reproductive success because of the low number of successfully delivered offspring in middleaged mice. 68 On the other hand, mice deficient in Cry1 or Cry2 have accelerated agerelated decline in fertility, as judged by the pregnancy rates in comparison with agematched wildtype mice, but it was rescued by the adjustment of the light-dark cycles to match with the endogenous circadian rhythms. 69 The effects of environmental perturbations and conse quent disruption of circadian clock on reproductive function have tested as well.…”
mentioning
confidence: 99%